Prevalência, perfil de suscetibilidade e caracterização molecular de Staphylococcus aureus isolados de uma linha de ônibus do sistema de transporte público coletivo do município de Goiânia-GO - Neves, Lorrane Souza (2016)
Staphylococcus aureus is an important agent of health care and community infections. Environmental surfaces, especially those in frequent contact with the hands, can serve as reservoirs of microorganisms, working as fomites in microbial spread. In the public transportation system, contact surfaces with hands can act as transmission vehicles, assisting the dispersion of S. aureus in the community. The aim of this study was to determine the prevalence of S. aureus and methicillin resistant S. aureus (MRSA) in buses, terminals and platforms of a larger route of the public transportation system in the city of Goiânia-GO, to determine the susceptibility and virulence profiles and assess the genetic similarity among S. aureus isolates. We collected 852 swabs fromhandrails of buses and ratchets of platforms and terminals that compose the East-West line. The isolation of staphylococci was done by standard techniques and species identification by detection of the femA gene. S. aureus identified were submitted to antimicrobial susceptibility testing, conventional PCR for detection of mecA and lukS-Fgenes, multiplex PCR to detect virulence factors genes, SCCmec typing and PFGE to assess the genetic similarity among strains. The contamination prevalence of handrails and ratchets by S. aureus was 17.7% (151/852). MRSA was detected in 0,5% of samples. The phenotype known as iMLSB was detected in 41.0% (62/151) of the isolates. Several virulence profiles were detected in 43 (28.5%)isolates, PFGE analysis revealed extensive genetic diversity of circulating strains, including MRSA strains similar to USA300 and USA800. The results suggest that S. aureus and MRSA strains, showing different susceptibility and virulence profiles are circulating in the community. They may be transmitted between individuals through fomites, putting the user population of the service at risk.